Efektivitas Pelatihan Dan Pengembangan Sumber Daya Manusia Untuk Meningkatkan Kualitas Pendidikan di TK PKK Majidi - masbullah, Masbullah; Salmi Yuniar Bahri; Moh. Juhad (OPTIMAL Jurnal Ekonomi dan Manajemen, 2024)
This study aims to investigate Human Resource Development management as an effort to improve the quality of education at TK PKK Majidi. The study involves 10 teachers from TK PKK Majidi as its subjects. The results indicate improvement, although not yet fully optimal. The school principal endeavors to enhance teacher quality by prioritizing HR development and skills training. Therefore, the next HR development strategy involves mandatory monthly training sessions for teachers. There are various types of training available for teachers to enhance their skills and competencies, ranging from leadership training, skills development, motivation, creativity, to participation in children's training activities. The findings suggest that when children become creative, teachers have achieved good quality in creative education.